Characterization of extended-spectrum cephalosporins and fluoroquinolone resistance of a Salmonella enterica serovar Thompson isolate from ready-to-eat pork product in China - Li, Lili; Olsen, Rikke Heidemann; Xiao, Jian; Liang, Meidan; Meng, Hecheng; Peng, Shifu (Frontiers in Microbiology, 2022)
Salmonella enterica displaying resistance to extended-spectrum cephalosporins (ESCs) and fluoroquinolone (FQs) has been deemed a high-priority pathogen by the World Health Organization. Co-resistance to ESCs and FQs have been reported in Salmonella enterica serovar Thompson (S. Thompson). However, the genetic context of ESCs and FQs resistance genes in S. Thompson lacks sufficient characterization. In this study, we characterized a multi-drug resistant (MDR) S. Thompson isolate recovered from a retail ready-to-eat pork (RTE) product in China. Short- and long-read sequencing (HiSeq and MinION) of the genome identified the presence of blaCMY-2, qnrS1, qepA8, along with 11 additional acquired antimicrobial resistance genes, residing on a 152,940 bp IncA/C plasmid. Specifically, the blaCMY-2, qnrS1, qepA8 genes were located in insertion sequences (ISs) and integron mediated mobile genetic structure, sugE-blc-blaCMY-2-ISEc9, IS26-orf6 -qnrS1-orf5-ISKpn19, intl1-qepA8-orf10-IS91-orf1-dfrA12-orf11-aadA2- qacE△1-sul1, respectively. Each of the genes were identified in various bacteria species, indicating their highly transfer ability. The plasmid was found to be transferable to Escherichia coli J53 by conjugation and resulted in the acquiring of multiple resistance in the transconjugants. The plasmid is closely related to plasmids from two human S. Thompson strains isolated in different region and year in China. Moreover, core-genome Multi Locus Sequence Typing (cgMLST) and phylogenetic analysis based on global 1868 S. Saintpaul isolates showed the S. Thompson isolate was highly epidemiologically linked to a human isolate in China. Our findings suggest that Chinese RTE pork products are a possible source of human pathogenic ESCs and FQs co-resistant S. Thompson. Furthermore, the results underline the important role of conjugative plasmids for acquiring and transmission of ESCs and FQs resistance in S. Thompson isolates, which need continuous investigation.